Relação entre força muscular e o desempenho físico em jogadores de futsal universitário - Oliveira, Lucas Silva de (Brasil, 2025)
This study investigated the relationship between lower limb muscle strength and physical performance in university futsal players. The sample consisted of 14 athletes from the futsal team of the Federal University of Amazonas (age: 20.80 ± 2.60 years; height: 1.74 ± 0.07 m; body weight: 71.53 ± 10.04 kg), all with a minimum of two years of experience in the sport. Strength tests (1RM) were applied in the bilateral and unilateral (dominant) squat, and the power and speed tests, countermovement jump (CMJ), squat jump (SJ), 10 and 30 m sprint and agility test (T test). The 1RM test in the bilateral squat showed a significant correlation with the CMJ (p = 0.02; r = 0.61) and SJ (p = 0.02; r = 0.60). The 1RM test in the unilateral squat correlated positively and significantly with the CMJ (p = 0.01; r = 0.73) and SJ (p = 0.01; r = 0.7). In the 30-meter sprint, there was a negative and significant correlation with the 1RM in the unilateral squat (p = 0.02; r = -0.61). It is concluded that the muscular strength of the lower limbs is related to performance in activities that require power and speed. Therefore, it is recommended that training programs include exercises aimed at developing maximum strength and muscular power to improve performance in sports such as futsal.